Total Forest Management (TFM) an Innovative Approach for Conservation of Natural Forests with Human Face - Sharma, R. C. (Indian Forester, 1997)
With the ever increasing anthropogenic impact, the life support system of the earth is under constant pressure. The adverse effect is reflected by way of natural resource degradation, leading to reduction in productivity which ends up in enhanced poverty and misery. Poverty, malnutrition and illiteracy are the main causes of population growth that further accentuates the degradation process. This, ultimately forms a vicious circle of natural resource degradation including forests. To conserve our forests, by and large, foresters concentrated on ’tree’, without appreciating the interdependence of various facets of the vicious circle. Forestry is not an end in itself. It ought to be looked as an integral part of the ecosystem, operating within the social, political and economic framework. Forestry is for people. Since traditional forestry management focussed only on single aspects of the vicious circle, no tangible achievements in respect of reversing or arresting the trend of degradation were forthcoming. The Total Forest Management (TFM) is an innovative approach for conservation of forests, which attempts to address the malady in totality by keeping ’people’ in the centre. The local people, local resource and local technology constitute the cornerstones of the green triangle which operates within the socio’political milieu so that the human aspect is taken care of. The system is being tried in five different areas of Madhya Pradesh by developing a package of ’hardware’ of physical activities and ’software’ of human sensitivities, which help in productivity enhancement through on farm and off farm activities. Non-Timber Forest Products (NTFP), with its attendant instrumentalities constitute the back bone of the system. The result is that the forest dwellers are not mere passive recipients of the programme but have become active partners in the endeavour and in many cases even proud owner of the hardware.